Comparison of impact characteristics of different ice hockey arena dasher boards - Poutiainen, Piritta (2012)
During last years the incidence and severity of ice hockey related concussions have been increased and, hence, something should be done to stop this growth. The main aim of this study was to find out how dasher board materials and structures affect impact characteristics and, thereby, the risk of concussions. The measurements were divided into two parts; in the first part, the physiological characteristics of body checks were determined in real game measurements, and the second part, consisted of simulation of body checks in the laboratory. High speed cameras and accelerometers were used to collect data. More flexible protective shielding material (dasher board B) resulted in lower peak force and stiffness as well as greater stopping distance compared to the other dasher boards. However, the dasher board with flexible protective shielding material including shielding supporting posts resulted to be non-consistent and, thereby, that kind of dasher boards cannot be classified as safe ones. Single-framed dasher board was detected to be more flexible than dual-framed counterpart and heavier protective shielding resulted in significantly higher element stiffness (p < .05). With this study it was shown that modification of the materials and structures of the dasher boards give an opportunity to affect impact characteristics and, thereby, the concussion risk. In the light of the results and the epidemiology of concussions it seems that the most safety dasher board would be single-framed with light and flexible protective shielding material and it would not include shielding supporting posts. However, there are still many questions under debate and, therefore, the investigation must be continued.